Clinical significance of the controlling nutritional status (CONUT) score in gastric cancer patients: A meta-analysis of 9,764 participants - Liu, Hui; Yang, Xiao-Chuan; Liu, Ding-Cheng; Tong, Chao; Wen, Wen; Chen, Ri-Hui (Frontiers in Nutrition, 2023)
Background: The clinical value of the controlling nutritional status (CONUT) score has been widely reported in multiple malignancies. The aim of this study is to investigate the association between the CONUT score and clinical outcomes in patients with gastric cancer. Methods: A comprehensive literature search of electronic databases including PubMed, Embase and Web of Science was performed up to December 2022. The primary endpoints were survival outcomes and postoperative complications. Subgroup analysis and sensitivity analysis were performed during the pooled analysis. Results: Nineteen studies including 9764 patients were included. The pooled results indicated that patients in the high CONUT group had a worse overall survival (HR= 1.70 95%CI: 1.54-1.87; P<0.0001; I2=33%) and recurrence-free survival (HR=1.57; 95%CI: 1.36-1.82; P<0.0001; I2=30%), and a higher risk of complications (OR=1.96; 95%CI: 1.50-2.57; P<0.0001; I2=69%). In addition, a high CONUT score was significantly associated with larger tumor size, higher percentage of microvascular invasion, later TNM stage and fewer patients receiving adjuvant chemotherapy, but not with tumor differentiation. Conclusion: Based on existing evidence, the CONUT score could act as a valuable biomarker to predict clinical outcomes in patients with gastric cancer. Clinicians could use this useful indicator to stratify patients and formulate individual treatment plans.